The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1143/jpsj.66.2232
|View full text |Cite
|
Sign up to set email alerts
|

Electronic State and Magnetic Susceptibility in Orbitally Degenerate (J=5/2) Periodic Anderson Model

Abstract: Magnetic susceptibility in a heavy fermion system is composed of the Pauli term (χP) and the Van-Vleck term (χV). The latter comes from the interband excitation, where forbital degeneracy is essential. In this work, we study χP and χV in the orbitally degenerate (J = 5/2) periodic Anderson model for both the metallic and insulating cases. The effect of the correlation between f -electrons is investigated using the self-consistent second-order perturbation theory. The main results are as follows. (i) Sixfold de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
(32 reference statements)
1
18
0
Order By: Relevance
“…When N f is larger than the number of conduction band N c , almost unhybridized f -levels exist near the Fermi level, except when the crystal-field splitting is very large. This situation induces a huge anomalous Hall coefficient [277] as well as the large Van Vleck susceptibilities [303,304] in Kondo insulators and in singlet SC heavy-fermion systems.…”
Section: Fermi Arc Picture and Transport Phenomenamentioning
confidence: 99%
“…When N f is larger than the number of conduction band N c , almost unhybridized f -levels exist near the Fermi level, except when the crystal-field splitting is very large. This situation induces a huge anomalous Hall coefficient [277] as well as the large Van Vleck susceptibilities [303,304] in Kondo insulators and in singlet SC heavy-fermion systems.…”
Section: Fermi Arc Picture and Transport Phenomenamentioning
confidence: 99%
“…We expect this intrinsic AHE is widely observed since the J =5/2 PAM is a well-established effective model for Ce-based HF systems: For example, it could explain a large Van-Vleck susceptibility in the Kondo insulator. 47,48 There remains a lot of work to be done on the AHE in HF systems. For example, Nakajima et al found that the AHC in the two-dimensional HF system CeMIn 5 ͑M =Co,Rh,Ir͒ is negligibly small.…”
Section: Comparison With Experiments: Heavy Fermionsmentioning
confidence: 99%
“…In the next stage, we study the KW relation in the weak coupling region (1/z > ∼ 1) using the second-orderperturbation-approximation (SOPA) with respect to U , both for J = 1/2 case and J = 7/2 case [17]. In the numerical calculation, we use the spherical Brillouin zone (|k| ≤ π) for simplicity of the numerical calculation.…”
mentioning
confidence: 99%
“…We note again that E f > µ in the present calculation by considering the particle-hole transformation for 4f 13 -electrons in Yb 3+ (J=7/2). In the case of U = 2, the DOS around the Fermi level and E f level are renormalized within a smaller energy width due to the ǫ-dependence of ReΣ(ǫ) [17,20].…”
mentioning
confidence: 99%